SINERGITAS HUKUM ADAT DAN PERATURAN DAERAH DALAM PENGENDALIAN DAMPAK PARIWISATA TERHADAP PURA AGUNG BESAKIH DI KABUPATEN KARANGASEM - Wijaya, I Made Hendra; Jaya, I Made Asmara; Sudiatmika, I Putu Bagus Merling (Institut Hindu Dharma Negeri Denpasar, 2019)
Synergy of Customary Law and Regional Regulation in Controlling the Impact of Tourism on the Besakih Agung Temple in Karangasem Regency can be seen with the issuance of the Bali Governor Regulation No. 51 of 2016 concerning Management of the Besakih Agung Temple and Pararem Besakih Indigenous Village with number 38 / DAB / IX / 2017, which regulates the existence of Operational Management (MO) Managing the Agung Besakih Temple Area for tourism control over the Agung Besakih Temple in Karangasem Regency